2021
DOI: 10.17221/17/2021-pps
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bioinsecticides on the grey maize weevil Tanymecus dilaticollis

Abstract: Tanymecus dilaticollis is an important pest of maize and sunflowers in eastern Europe. In the present study, we examined the effectiveness of two commercially available bioinsecticides against T. dilaticollis adults under laboratory conditions: Naturalis<sup>®</sup> based on the Beauveria bassiana fungus and an azadirachtin-based botanical product NeemAzal T/S<sup>®</sup>. Our results suggested that adults of the pests are more susceptible to B. bassiana than to azadirachtin. Naturalis&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Recently, crataegi Germar 1824, but it was significantly higher than the mortality in the control variant (sterile water) after 28 days post treatment (Hirsch and Reineke, 2014). Toshova et al (2021) reported high (˃ 86%) lethal effect of Naturalis® at concentrations above 2.3 × 10 4 conidia/ ml on T. dilaticollis adults under laboratory conditions. Naturalis® have been showed to be effective in field/ semifiled conditions against several coleopteran pests (Paparatti and Speranza, 2005;Ladurner et al, 2009;Hirsch and Reineke, 2014;Sufyan et al, 2017;Toshova et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, crataegi Germar 1824, but it was significantly higher than the mortality in the control variant (sterile water) after 28 days post treatment (Hirsch and Reineke, 2014). Toshova et al (2021) reported high (˃ 86%) lethal effect of Naturalis® at concentrations above 2.3 × 10 4 conidia/ ml on T. dilaticollis adults under laboratory conditions. Naturalis® have been showed to be effective in field/ semifiled conditions against several coleopteran pests (Paparatti and Speranza, 2005;Ladurner et al, 2009;Hirsch and Reineke, 2014;Sufyan et al, 2017;Toshova et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…Laboratory assessment of entomopathogenic fungi is an important step in determining pathogenic strain prior to use in the field for insect pest control. The insecticide activity of B. bassiana strain ATCC 74040 on other important pest of maize in Eastern Europe, the grey maize weevil, Tanymecus dilaticollis Gyllenhal, 1834 (Curculionidae), have been demonstrated under laboratory and field conditions (Toshova et al, 2021). The present study aimed to investigate the effectiveness of Naturalis® against WCR adults and larvae and adults of CLB under laboratory conditions.…”
Section: Asproparthenis Punctiventrismentioning
confidence: 99%